1986
DOI: 10.1055/s-2007-1012338
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus: A Syndrome with Phenotypic and Genotypic Heterogeneity

Abstract: One hundred ninety-nine gravida with gestational diabetes mellitus (GDM) defined as "carbohydrate intolerance of varying severity with onset or first recognition during pregnancy" have been stratified into subgroups on the basis of fasting plasma glucose and evaluated for further phenotypic and genotypic heterogeneity. A significantly greater proportion of the women in all our groups were older and heavier than in a "control" population of 148 consecutive gravida with documented normal oral glucose tolerance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
4
18
0
Order By: Relevance
“…Although classical MHC class II molecules HLA-DR3 and DR4 were not found to be related to GDM [20], recent studies have found genetic evidence from PPARG, KCNJ11, TCF2/HNF1B, and WFS1 or HNF4A that is related to dysfunctional pancreatic b-cell secretion and GDM, suggesting new possibilities for the study of GDM [21, 22]. …”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Although classical MHC class II molecules HLA-DR3 and DR4 were not found to be related to GDM [20], recent studies have found genetic evidence from PPARG, KCNJ11, TCF2/HNF1B, and WFS1 or HNF4A that is related to dysfunctional pancreatic b-cell secretion and GDM, suggesting new possibilities for the study of GDM [21, 22]. …”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…This 'fuel mediated teratogenesis' induces fetal hyperglycemia, subsequent hyperinsulinemia and promotes fetal adiposity [92,93].…”
Section: Insulin and The Potential For Aberrant Fetal Growthmentioning
confidence: 99%
“…Freinkel et al (56) examined whether HLA antigens were associated with GDM. They observed that HLA DR3 and DR4 antigens were uncommon overall, but nonetheless in higher frequency in women with GDM than in women with normal pregnancies.…”
Section: Candidate Genesmentioning
confidence: 99%